Analysis and Simulation of Gradeability of Orchard Operation Platform Based on ADAMS. Issue 4 (June 2019) - Hao, Zhang; Guiju, Fan; Zhao, Li; Fu, Qin; Xiaohan, Sun
Abstract: In view of the instability of the orchard machinery in the hilly terrain in China, this paper takes a crawler orchard operation platform as the research object. On the basis of mechanical design and theoretical analysis, the model is created by Solidworks and imported into ADAMS. It performs kinematics simulation and obtains experimental data of the machine running on a slope with a certain gradient. The simulation experiment sets the slope angle between 0° and 35°, and displays the climbing ability and working state of the orchard work platform by changing the driving force of the engine. The simulation results show that the orchard work platform designed in this paper can be used to carry out the work in the hilly area with large slope, which provides effective parameters for the improvement and actual operation of the machine.